2019
DOI: 10.3390/md17020073
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Potential Biological Applications of Haloaryl Secondary Metabolites from Macroalgae

Abstract: Macroalgae have been reported as an important source of halogenated aromatic secondary metabolites, being the majority of these derivatives isolated from red algae. Halophenols and haloindoles are the most common haloaryl secondary metabolites isolated from these marine organisms. Nevertheless, some halogenated aromatic sesquiterpenes and naphthalene derivatives have also been isolated. Most of these secondary metabolites showed interesting biological activities, such as antitumor, antimicrobial, antidiabetic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 61 publications
0
50
0
1
Order By: Relevance
“…The search for novel compounds from marine organisms in recent years has produced a number of novel secondary metabolites with pharmaceutical, cosmetics, traditional, and industrial applications [9]. Among these natural products of marine origin, the isolation of halogenated derivatives, especially the bromophenols from seaweeds and macro-algae has been exhaustively reported [10,11]. Recent studies showed that the marine BPs demonstrated a wide range of biological activities [12][13][14][15][16], and therefore the novel BPs have attracted much attention in the field of pharmaceutical agents and functional foods [11].…”
Section: Introductionmentioning
confidence: 99%
“…The search for novel compounds from marine organisms in recent years has produced a number of novel secondary metabolites with pharmaceutical, cosmetics, traditional, and industrial applications [9]. Among these natural products of marine origin, the isolation of halogenated derivatives, especially the bromophenols from seaweeds and macro-algae has been exhaustively reported [10,11]. Recent studies showed that the marine BPs demonstrated a wide range of biological activities [12][13][14][15][16], and therefore the novel BPs have attracted much attention in the field of pharmaceutical agents and functional foods [11].…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated compounds are also an interesting set of bioactive macroalgae secondary metabolites [17,[110][111][112][113]. Among these, halogenated terpenes and bromophenols are those whose in vivo studies revealed the greatest potential for new drug development, as discussed below.…”
Section: Halogenated Secondary Metabolitesmentioning
confidence: 99%
“…It is therefore important to discover compounds that inhibit the AI-2 system for control of bacterial virulence and biofilm formation. Several compounds have been shown to inhibit AI-2 based QS of Vibrio spp., including halogenated furanones, cinnamaldehyde, and their derivatives [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed is one of the most available sources of bioactive compounds in the marine plant kingdom [12]. Seaweed produces a diversity of bioactive compounds, such as saturated and polyunsaturated fatty acids, vitamins, amino acids, polyphenol, alkaloids, halogenated compounds, and polysaccharides such as agar, carrageenan, proteoglycans, alginate, laminaran, rhamnan sulfate, and fucoidan [9,13]. Gracilaria genus is a macroalgae group with more than 300 species, of which 160 have been accepted taxonomically [14].…”
Section: Introductionmentioning
confidence: 99%